A Literature Review on the Application of Evaluation Design in English Educational Settings - Elida, Yusti; Ambiyar, Ambiyar; Oktadela, Resy (UIR Press, 2025)
Evaluation design plays a crucial role in enhancing English language education by assessing program effectiveness and improving teaching practices. While evaluation has gained increasing attention in educational settings, gaps remain between theoretical frameworks and their practical implementation. This literature review examines the application of evaluation design in English education, focusing on formative and summative approaches. It explores key models such as Kirkpatrick’s Four-Level Model and Scriven’s Goal-Free Evaluation, alongside methodologies commonly used in assessing language programs. The review also highlights challenges educators face in integrating evaluation into teaching, including aligning assessments with curriculum objectives and addressing diverse learner needs. The findings suggest that contextual factors, such as institutional policies, student proficiency levels, and pedagogical goals, significantly influence evaluation effectiveness. This study contributes to the field by providing a clearer understanding of how adaptable evaluation frameworks can bridge the gap between theory and practice, ultimately supporting more effective language teaching and learning.